Ovarian tissue cryopreservation for an 8 year old girl after hematopoietic stem cell transplantation in China: case report and literature review - Zecheng Wang; Xiangyan Ruan; Juan Du; Fengyu Jin; Muqing Gu; JiaoJiao Cheng; Yanqiu Li; Yanglu Li; Lili Liu; Yurui Wu; Alfred O. Mueck (Gynecological Endocrinology)
Background Preconditioning before hematopoietic stem cell transplantation (HSCT) severely damages ovarian function, resulting in infertility and premature ovarian insufficiency (POI) in young women and girls. Ovarian function and fertility preservation before HSCT is crucial. In China, many patients miss this opportunity, highlighting the need for ovarian function and fertility preservation after HSCT. Ovarian tissue cryopreservation (OTC) is a standard method for fertility preservation and protecting ovarian function. The objective of this case report is to report a case of OTC performed on an 8-year-old girl after HSCT, and present a review about the necessity and feasibility of ovarian preservation after HSCT.Case An 8-year-old girl required a second HSCT due to a relapse of dermatomyositis. Before the procedure, she visited our center for OTC. Hormonal assessments showed FSH 1.17 IU/L, LH 0.00 IU/L, E2 < 11.80 pg/ml, and AMH 0.81 ng/ml. Pelvic ultrasound revealed bilateral ovarian sizes of approximately 1.5 × 0.7 × 0.7 cm and 1.6 × 0.9 × 0.7 cm, with 10 and 4 visible follicles, respectively. We proceeded with OTC, surgically retrieving the entire left ovary via laparoscopy. Seven ovarian cortical slices were cryopreserved by slow freezing, with an average of 1079 follicles in per 2 mm diameter cortical tissue slice.Conclusion Patients who miss fertility preservation before HSCT should consult fertility preservation and gynecological endocrinology experts as early as possible after HSCT and undergo regular follow-up. If clinical evidence indicates residual ovarian function, fertility protection measures should be discussed promptly. OTC should be assessed as a successful option for women after HSCT.